The role of educational institutions in transformations to achieve sustainable development - Olha Kurylo; Olena Kryvylova; Viktoriia Zhyhir; Valentyna Peregudova; Yuliia Bielova-Oleynik; Serhii Onyshchenko; Olena Revutska (Problems and Perspectives in Management)
The study aims to assess the role of educational institutions in achieving sustainable development goals (SDGs) during wartime in Ukraine. The focus is on the education sector, namely, adapting educational strategies to contemporary challenges. The paper employs a content analysis of information published by ten leading pedagogical universities in Ukraine to assess their success in implementing sustainable development goals. Special attention is given to such sustainable development goals as quality education (SDG 4), gender equality (SDG 5), sustainable cities and communities (SDG 11), peace and justice (SDG 16), and partnerships for the goals (SDG 17). University strategies and publication activity on addressing global sustainable development challenges in the Scopus database were analyzed. The research results demonstrate the variability of university development strategies, which determines their uneven focus on certain aspects of sustainable development. The results highlight the need to improve management strategies, integrate sustainable development principles into educational programs, and strengthen international partnerships. Finally, the study offers recommendations for further adaptation of educational institutions to changing conditions to ensure the sustainable development of Ukrainian society.